2022
DOI: 10.3390/molecules27165255
|View full text |Cite
|
Sign up to set email alerts
|

Tri- and Pentacyclic Azaphenothiazine as Pro-Apoptotic Agents in Lung Carcinoma with a Protective Potential to Healthy Cell Lines

Abstract: The phenothiazine derivatives, tricyclic 10H-3,6-diazaphenothiazine (DPT-1) and pentacyclic 7-(3′-dimethylaminopropyl)diquinothiazine (DPT-2), have recently been shown to exhibit promising anticancer activities in vitro. In this report, we demonstrated that DPT-1 and DPT-2 could be pro-apoptotic agents in lung carcinoma, the human lung carcinoma A549 and non-small lung carcinoma H1299, in the range of IC50 = 1.52–12.89 µM, with a protective potential to healthy cell lines BEAS-2B and NHDF. The compounds showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…Also, azaphenothiazine substituted with dialkylaminoalkyl or cyclicaminoalkyl as a pharmacophoric group containing a ChemistrySelect www.chemistryselect.org lipophilic chain has shown good cytotoxic potential toward various cancer cell lines such as T98G (malignant brain cancer), H460 (lung cancer), SNU80 (thyroid cancer), T47D (ductal carcinoma) and A549 (lung cancer). [36][37][38] Encouraged by these findings and as part of our research work on exploring anticancer activity of novel heterocyclic compounds, [39][40] we have synthesized 1-azaphenothiazine and its 10-(2'-morpholinylethyl) derivatives substituted at 3-and 8-positions with different groups (Cl, Br, CF 3 , and Me) and examined their anticancer activities toward various cancer cell lines such as colon cancer cells (CaCO2), lung cancer cells (A549), pancreatic cancer cells (SW1990, SW48), and human breast cancer cells (MDA-MB-231, MCF-7).…”
Section: Introductionmentioning
confidence: 99%
“…Also, azaphenothiazine substituted with dialkylaminoalkyl or cyclicaminoalkyl as a pharmacophoric group containing a ChemistrySelect www.chemistryselect.org lipophilic chain has shown good cytotoxic potential toward various cancer cell lines such as T98G (malignant brain cancer), H460 (lung cancer), SNU80 (thyroid cancer), T47D (ductal carcinoma) and A549 (lung cancer). [36][37][38] Encouraged by these findings and as part of our research work on exploring anticancer activity of novel heterocyclic compounds, [39][40] we have synthesized 1-azaphenothiazine and its 10-(2'-morpholinylethyl) derivatives substituted at 3-and 8-positions with different groups (Cl, Br, CF 3 , and Me) and examined their anticancer activities toward various cancer cell lines such as colon cancer cells (CaCO2), lung cancer cells (A549), pancreatic cancer cells (SW1990, SW48), and human breast cancer cells (MDA-MB-231, MCF-7).…”
Section: Introductionmentioning
confidence: 99%
“…Such a group of 2 modified phenothiazines includes dipyridothiazines having two pyridine rings in their structure instead of benzene rings [21]. Dipyridothiazines show valuable anticancer activities involving induction of apoptosis via mitochondrial activation of it as well as partial DNA intercalation [25][26][27]. Dipyridothiazines also showed significant immunosuppressive and anti-inflammatory activity by inhibiting TNF alpha and interleukin 6 levels [28].…”
Section: Introductionmentioning
confidence: 99%
“…The weak lethal effect observed in NHDF or BEAS-2B cells at IC 50 doses against A549 or H1299 cells confirms promising cancer selectivity. The cell cycle revealed that substance 2 activated the necrosis phase [ 25 ].…”
Section: Introductionmentioning
confidence: 99%